The role of the Constitutional Court in protecting public rights and freedoms. (Numerus academy review, 2026)
The issue of constitutionalizing rights and public liberties within the content ofthe constitution is one of the most important guarantees granted to their exercise within the framework of the law.This study aims to clarify the scope of the constitutional court's control in thefield of protection of public rights and freedoms, and to emphasize the need toreconcile the protection of these rights and freedoms with the discretion of thelegislator.